Pluralisme Agama dan Implementasi Pendidikan Multikultural dalam Mewujudkan Konsep Masyarakat Madani di Indonesia - Achmad Anwar Abidin (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2018)
It is important to know and understand that religious pluralism and the implementation of multicultural education is one of the ikhtiyar for the realization of civil society in Indonesia. In this article the discussion will focus on the understanding of religious pluralism and the implementation of multicultural education in realizing the concept of civil society coveted by every nation. The methods undertaken in this discussion are library research on books and articles related to Pluralism, multicultural education, and civil society concepts from experts. The result of religious pluralism in Indonesia is a Sunnatullah that must be addressed with adult, especially for Muslims as the majority. Since Islam itself Acknowledges the existence of other religions, giving it the right to co-exist with respect for other religions, to avoid violence and to keep religious places of worship, not to impose the will of other faiths and Islam also recognizes the many ways that human beings can take and the government is competing in virtue. One way of instilling an understanding of religious pluralism is through multicultural education, but its implementation in Indonesia is still a new discourse that needs to be responded quickly to keep the multicultural nation rich in multicultural because multicultural education is a form of awareness about diversity. understanding of religious and cultural diversity requires new construction of justice, equality and a democratic society towards the realization of civil society in Indonesia.